At a meeting of the committee of the county of Lancaster, 5th July, 1776 : the committee taking into their consideration the important business of raising the quota of troops in this county . (Printed by Francis Bailey, in King-Street, 1776)
July 5, 1776 Resolutions dealing with military issues and defense from a meeting of the Lancaster County Committee of Observation.